PENGARUH WAKTU PENGELASAN TITIK (SPOT WELDING) TERHADAP KEKERASAN, KEKUATAN GESER DAN DIAMETER NUGGET PADA BAJA SPCEN 1,6 mm - Riantono Rasyid; Novi Sukma Drastiawati (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2020)
The development of technology in manufacturing is currently very fast. One of the important processes involved is joining, including the process of resistance spot welding or better known as spot welding. The use of point welding has several advantages, including a neat shape of the joint, the process is faster, the connection is tighter and the operation is relatively easy and does not require filler metal. The connection of relatively thin plate-shaped steel using resistance spot welding is an alternative option that is widely used by the automotive parts production industry. However, there are no data regarding the best time and data regarding the hardness test, nugget diameter, and shear test on SPCEN steel material. This study aims to determine the effect of spot welding time on hardness, shear strength and nugget diameter on SPCEN steel material. This study used an experimental method with a time variable of 1 second, 2 seconds and 3 seconds with standard material SPCEN JIS G 3141, standard hardness testing using DIN 50103 and standard shear testing using ASTM D 1002. equal that is 3.3 mm. The lowest average nugget hardness results are found on steel plates marked with the name ABC, time of 1 second with an average nugget hardness of 116.6 HRB and the highest average nugget hardness is found on GHI steel within 3 seconds with an average nugget hardness of 117 , 9 HRB. The lowest average yield of shear strength is found in ABC steel at 1 second with a maximum shear strength of 294.82 N / m² and a maximum load of 1592.01 Newton, the highest average yield of shear strength is found on steel plates marked with the name GHI time 3 seconds with a maximum tension of 415.89 N / m² and a maximum load of 2245.83 Newton. Thus the longer the spot welding time (spot welding), the greater the current used, the greater the heat generated and the hardness and shear strength become stronger. Shows the best time for spot welding (spot welding) of 1.6 mm SPCEN steel plate in 3 seconds.